(untitled) (LEARNing Landscapes, 2021)
This article emerges from an approach to transformative learning where students are challenged to explore taken-for-granted assumptions about their experiences in the world. We outline the 6-Part Story Method (6PSM), which uses abstract images to provide a structured storytelling process that enables reflexive learning. This is documented through conversations between a university teacher and three Masters students about the method used in their course on practical ethics in process consulting. Using individual stories that emerged from a common set of cards, we illustrate how the method enabled us to critically explore our practices as teacher and student consultants.